Effect on Hepatic Parameters and Hepatocytes following administration of antihypertensive, hypolipidemic and hypoglycemic drugs in combination (Part II) - Afshan Siddiq and Rafeeq Alam Khan (Journal of Applied Pharmaceutical Science, 2013)
Liver damage is the serious additive effect of drugs used for the treatment of patients suffers from diabetes, hypertension and hyperlipidemia. In continuation of our previous published research the present study is done to evaluate the toxic effects of combination of drugs prescribed for above stated diseases. Combinations of drugs were given to rabbits for the period of two months and their effects on liver function tests were observed. As compared to control rabbits, the combination Acarbose, Lisinopril and Atorvastatin showed increased Glutamic-Pyruvic Transaminase (GPT), Alkaline Phosphatase (ALP) and Gamma glutamyl transferase (γ-GT) (p
Keywords: Multiple drugs, hypoglycemia, hyperlipidemia, antihy